P425 Capturing missed opportunities for PrEP prescription in patient diagnosed with other STIs. (14th July 2019) - Mclaughlin, Stephanie; Pitts, Robert; Kapadia, Farzana; Greene, Richard
Abstract : Background: Sexually transmitted infection (STI) testing in hospital-based settings represents an opportunity to intervene and prescribe pre-exposure prophylaxis (PrEP) to prevent HIV infections. Methods: Electronic health records of patient visits at NYC Health+Hospitals(H+H)/Bellevue between 1/1/14-7/30/17 were queried for positive STIs (gonorrhea (GC) and chlamydia (CT) & syphilis) results by hospital location and time. Visit data also included: patient demographic characteristics and PrEP prescriptions. Generalized estimating equations using a logit link, to account for repeated within patient measures, were used to explore the relationship between having a medical follow-up visit in ≤30 and ≤90 days following STI testing, which represents an opportunity to provide PrEP prescription, and demographic factors, controlling for key confounders. Results: A total of 1, 169 HIV-negative patients with 1+ STI diagnosis contributed 1, 275 visits, of whom 700 (58%) were female with mean age of 32 yrs (SD=12.3)] and 532 (42%) were male with mean age of 44 yrs (SD 16.3). The majority of patients were Black (40%) or Hispanic/Latino (50%). In this sample, only 27 patients received PrEP. Overall, chlamydia was the most common (135/11%), followed by syphilis (476/38%) and gonorrhea (135/11%). Two-thirds of patients with a +STI diagnosis originated from the ED (33%) and OB/GYN clinics (32%); an additional 11% were diagnosed in Medicine clinics. 78% of patients did not have follow up ≤30 days after +STI diagnosis. In adjusted analyses, the adjusted OR for follow up ≤30 days after +STI diagnosis was lower for Black patients [0.39 (95%CI 0.21–0.72, p<0.01)] and higher for patients ≥45 years old 2.20 [(95%CI 1.16–4.19, p= 0.02)]. Conclusion: STI testing at a major, publicly-funded hospital within NYC H&H is an opportunity to discuss and prescribe PrEP. However, our findings suggest that there are significant missed opportunities for linkage to care after a +STI diagnosis and PrEP initiation, especially in the ED among young Black patients. Disclosure: No significant relationships.